A survey on lifestyle and awareness of the use of statins in a sample of cardiopathic patients. Issue 8 (13th September 2020) - Bernardini, Francesco; Gostoli, Sara; Marchetti, Gabriello; Grazi, Paola; Poci, Maria Grazia; Roncuzzi, Renzo; Rafanelli, Chiara
ABSTRACT: Current guidelines highlight the importance of lifestyle modification in the treatment of hypercholesterolemia, in addition to lipid-lowering drugs. However, patients taking statins do not always follow the physician's prescriptions on lifestyle change.. The present research aims to understand the psychological characteristics associated with unhealthy lifestyle change/maintenance among cardiopathic patients treated with statins. 58 patients were enrolled and evaluated by both observer- (clinical distress, psychosomatic syndromes) and self-rated (lifestyle, subclinical distress, well-being) measures. Ad-hoc items were included to evaluate self-perceived lifestyle changes and awareness about cholesterol-lowering effects of statins. 55.4% of the patients had not changed their lifestyle since taking statins and felt less contented (p < 0.05); 10.7% were unaware of the cholesterol-lowering effects of these drugs. Minor depression was the most frequent diagnosis(8.9%). It was significantly associated with the absence of lifestyle modification(p < 0.05), even though all minor depressed patients were aware of the effects of statins. On the contrary, those who were unaware showed significantly lower well-being (positive relations [p <0.05]; purpose in life [p<0.001]). Minor depression and psychological well-being impairments should thus be assessed in patients taking statins in order to recognize potential psychological risk factors associated with maintenance of unhealthy behaviors. .